The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/biolog-2017-0157
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a HSP40 gene involved in planarian regeneration

Abstract: Heat shock protein 40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The siRNA studies showed that the major tissues and organs replaced after OS amputation-the OPO, CMB, and siphon lobes could be suppressed by knockdown of the hsp70 and dnaJb4 genes, but not the bag3 gene, suggesting that BAG3 is not required for regeneration. The results are consistent with demonstrations of the importance of similar heat shock genes in other regenerating systems, including planarian whole body regeneration [ 42 , 43 ], starfish arm regeneration [ 44 ], zebrafish fin regeneration [ 45 ], Xenopus tadpole hindlimb regeneration [ 46 ], and mouse liver regeneration [ 47 ]. Our studies contribute a new understanding of the process of Ciona unidirectional regeneration by identifying stress in the BS as a key event necessary for initiating the distal regeneration program.…”
Section: Discussionsupporting
confidence: 87%
“…The siRNA studies showed that the major tissues and organs replaced after OS amputation-the OPO, CMB, and siphon lobes could be suppressed by knockdown of the hsp70 and dnaJb4 genes, but not the bag3 gene, suggesting that BAG3 is not required for regeneration. The results are consistent with demonstrations of the importance of similar heat shock genes in other regenerating systems, including planarian whole body regeneration [ 42 , 43 ], starfish arm regeneration [ 44 ], zebrafish fin regeneration [ 45 ], Xenopus tadpole hindlimb regeneration [ 46 ], and mouse liver regeneration [ 47 ]. Our studies contribute a new understanding of the process of Ciona unidirectional regeneration by identifying stress in the BS as a key event necessary for initiating the distal regeneration program.…”
Section: Discussionsupporting
confidence: 87%
“…Fluorescent real time RT-PCR (qRT-PCR) was performed three times with independent RNA samples. Planarian elongation factor 2 ( Djef2 ) was utilized as the reference gene in all of the experiments ( Ma et al, 2017 ). Expression ratios were determined with the 2 −ΔΔCT method, which was described by Livak and Schmittgen (2001) .…”
Section: Methodsmentioning
confidence: 99%